Boosting ESG Performance: Overcoming Collusion Among Entrepreneurial Family and Institutional Shareholders - Geraldina, Ira; Muktiyanto, Ali; Rahardja, Untung (Aptisi Transactions On Technopreneurship (ATT), 2025)
This study addresses the debate on the role of Multiple Large Shareholders (MLS) in influencing Environmental, Social, and Governance (ESG) performance in family-controlled firms across ASEAN. It explores whether MLS identity creates a collusion effect or monitoring effect on ESG outcomes. Using unbalanced panel regression with 672 firm-year observations from publicly listed firms in ASEAN-6 (2015-2022), this study evaluates the impact of MLS identity on ESG performance. The findings indicate that MLS mainly exert a collusion effect, prioritizing private gains over stakeholder interests. Institutional investors as second-largest shareholders often misuse private ESG information rather than ensuring accountability, amplifying the collusion effect. These results contrast with prior studies highlighting MLS monitoring role in other regions. This study emphasizes the need for stronger governance in ASEAN to address MLS collusion and improve ESG performance. Global investors and policymakers must advocate for sustainable practices and transparency in family-controlled firms. The insights advance discussions on ownership structures and their implications for corporate sustainability in emerging markets.